Orphan Three-Finger Toxins Bind at Tissue Factor–Factor VIIa Interface to Inhibit Factor X Activation: Identification of Functional Site by Docking - Choudhury, Manisha; McCleary, Ryan J. R.; Kini, R. Manjunatha; Velmurugan, Devadasan (TH Open, 2018)
Three-finger toxins (3FTxs) contribute to toxicity of venomous snakes belonging to the family Elapidae. Currently, functions of a considerable proportion of 3FTxs are still unknown. Here, we describe the function of orphan group I 3FTxs consisting of four members. We also identified a new member of this group by sequencing a transcript isolated from Naja naja venom. This transcript, named najalexin, is identical to that previously described 3FTx from Naja atra venom gland, and shared high sequence identity with ringhalexin from Hemachatus haemachatus and a hypothetical protein from Ophiophagus hannah (here named as ophiolexin). The three-dimensional structure, as predicted by molecular modeling, showed that najalexin and ophiolexin share the same conserved structural organization as ringhalexin and other 3FTxs. Since ringhalexin inhibits the activation of factor X by the tissue factor–factor VIIa complex (TF-FVIIa), we evaluated the interaction of this group of 3FTxs with all components using in silico protein–protein docking studies. The binding of orphan group I 3FTxs to TF-FVIIa complex appears to be driven by their interaction with TF. They bind to fibronectin domain closer to the 170-loop of the FVIIa heavy chain to inhibit factor X activation. The docking studies reveal that functional site residues Tyr7, Lys9, Glu12, Lys26, Arg34, Leu35, Arg40, Val55, Asp56, Cys57, Cys58, and Arg65 on these 3FTxs are crucial for interaction. In silico replacement of these residues by Ala resulted in significant effects in the binding energies. Furthermore, these functional residues are not found in other groups of 3FTxs, which exhibit distinct pharmacological properties.
Keywords: extrinsic tenase complex; anticoagulant; factor VIIa–tissue factor complex inhibitor; orphan group I toxins